Pengaruh Brand Ambassador K-Artist Dan Harga Terhadap Impulse Buying Produk Mie Lemonilo - Nyoman Sri Manik Parasari; Nuning Indah Pratiwi; Putu Ratna Juwita Sari; Ni Putu Swari Febrianti (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The development of Korean Wave in Indonesia has encouraged many Indonesian brands to partner with K-Artist as brand ambassador for their products, one of which is Mie Lemonilo. K-Artist fans are known for their loyalty. This can be seen from the selling out of Mie Lemonilo products within few hours of the product launch in several Indonesian e-commerce. This study aims to determine influence of brand ambassadors and prices partially and simultaneously on impulse buying Mie Lemonilo. The data collection technique used was questionnaire. The sample was 100 respondents. Data analysis technique used is Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient Determination Test, F test and t test. From the research results it’s known brand ambassadors have significant positive effect on impulse buying, prices have significant positive effect on impulse buying, simultaneously brand ambassadors and prices have significant effect on impulse buying. The magnitude of the influence of the independent variables on impulse buying is 52.7%. Suggestions that can be given are Lemonilo expected use brand ambassadors in promotions, work with well-known artists, have good image and ability to influence consumers Keywords: : Brand Ambassador, Price, Impulse Buying, Korean Wave